Crystallization behavior of co-polyesters based on hydroxy fatty acids extracted from tomato peel agro-wastes - Hallavant, Kylian; Esposito, Antonella; Bakan, Bénédicte; Lourdin, Denis; Saiter-Fourcin, Allisson (Polymer (Guilford), 2026)
This work investigates the crystallization behavior of bio-based slightly crosslinked polyester networks synthesized from long-chain hydroxy fatty acids. The crystallization kinetics and the melting behavior were assessed using a combination of modulated-temperature differential scanning calorimetry (MT-DSC) and fast scanning calorimetry (FSC). The characterization of the crystalline phases was performed by X-ray diffraction (XRD) and polarized-light optical (POM) microscopy. A methodology based on calorimetric investigations was used, allowing to estimate the theoretical value of the melting enthalpy Δhm0 of the initial cutin monomers as well as of the derived co-polyester networks. The results obtained by this method allowed to estimate the crystalline content Xc. The combination of XRD and calorimetric analyses evidenced the existence of polymorphs with different stabilities over time at room temperature, characterized by a monotropic transition from the metastable crystal phase (α-phase) to more stable crystal phases (β′and β-phases) depending on the crystallization time accorded to the monomers and the crosslinked co-polyesters. This work delves deeper into the complex crystallization behavior of biobased polyesters, which could eventually allow a better control over the properties of these materials. [Display omitted] •Melting behavior of bio-based slightly crosslinked polyester networks.•Theoretical value of melting enthalpy of the initial cutin monomers.•Theoretical value of melting enthalpy of the derived co-polyester networks.•Determination of the crystalline content Xc.